2019
DOI: 10.1002/ijgo.12800
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic therapy can inhibit growth of ovarian cancer cells and reverse chemoresistant properties acquired from metastatic omentum

Abstract: Objective To examine the cytotoxicity of epigenetic drugs independently and in combination with chemotherapy on ovarian cancer cells Caov‐3, and to investigate their ability to acquire chemoresistance in omental microenvironments and whether epigenetic drugs can counteract this chemoresistance. Methods A pilot study was conducted in Cooper University Hospital, NJ, USA from August 1 to October 31, 2017, among women undergoing surgeries for uterine and ovarian cancer. Cytotoxicity assays using IC50 values of epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Emerging evidence has indicated that cancer cells can adapt to environmental conditions through epigenetic mechanisms in response to their niche during tumor progression [ 38 ]. Epigenetic changes, including DNA methylation and miRNA-mediated silencing, primarily drive tumorigenesis and metastasis in multiple cancer types, including ovarian cancer [ 39 , 40 , 41 ]. In ovarian cancer, tumor suppressor genes or miRNAs are often silenced by epigenetic events, consequently promoting cancer proliferation, metastasis, and chemoresistance [ 24 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has indicated that cancer cells can adapt to environmental conditions through epigenetic mechanisms in response to their niche during tumor progression [ 38 ]. Epigenetic changes, including DNA methylation and miRNA-mediated silencing, primarily drive tumorigenesis and metastasis in multiple cancer types, including ovarian cancer [ 39 , 40 , 41 ]. In ovarian cancer, tumor suppressor genes or miRNAs are often silenced by epigenetic events, consequently promoting cancer proliferation, metastasis, and chemoresistance [ 24 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, tumor suppressor genes or miRNAs are often silenced by epigenetic events, consequently promoting cancer proliferation, metastasis, and chemoresistance [ 24 , 42 ]. The omental microenvironment is a major metastatic site and plays a key role in ovarian cancer peritoneal metastases [ 39 , 43 ]. Recent studies have reported aberrant epigenetic crosstalk between ovarian cancer cells and adipocytes in the omental metastatic TME, which contributes to the metastatic progression of ovarian cancer [ 5 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As Modesitt et al have suggested, the timing of epigenetic therapy with chemotherapy may be critical [44]. Sequential use of conventional chemotherapy and epigenetic drugs has been shown to decrease toxicity to normal cells while maintaining cytotoxicity in ovarian cancer cells in vitro [29]. This method has not been utilized in clinical trials involving epigenetic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The key prognostic factor for OC is the resistance of the patient’s tumor to chemotherapy, especially platinum-based drugs. Epigenetic drugs combined with paclitaxel and platinum are more effective than chemotherapy alone [ 13 ].…”
Section: Introductionmentioning
confidence: 99%